Perinatal care in SARS-CoV-2 infected women: the lesson learnt from a national prospective cohort study during the pandemic in Italy - Edoardo Corsi Decenti; Michele Antonio Salvatore; Donatella Mandolini; Letizia Sampaolo; Paola D'Aloja; the Italian Obstetric Surveillance System COVID-19 Consortium; Serena Donati (BMC, 2023)
Abstract Background Despite the growing importance given to ensuring high-quality childbirth, perinatal good practices have been rapidly disrupted by SARS-CoV-2 pandemic. This study aimed at describing the childbirth care provided to infected women during two years of COVID-19 emergency in Italy. Methods A prospective cohort study enrolling all women who gave birth with a confirmed SARS-CoV-2 infection within 7 days from hospital admission in the 218 maternity units active in Italy during the periods February 25, 2020-June 30, 2021, and January 1-May 31, 2022. Perinatal care was assessed by evaluating the prevalence of the following indicators during the pandemic: presence of a labour companion; skin-to-skin; no mother-child separation at birth; rooming-in; breastfeeding. Logistic regression models including women' socio-demographic, obstetric and medical characteristics, were used to assess the association between the adherence to perinatal practices and different pandemic phases. Results During the study period, 5,360 SARS-CoV-2 positive women were enrolled. Overall, among those who had a vaginal delivery (n = 3,574; 66.8%), 37.5% had a labour companion, 70.5% of newborns were not separated from their mothers at birth, 88.1% were roomed-in, and 88.0% breastfed. These four indicators showed similar variations in the study period with a negative peak between September 2020 and January 2021 and a gradual increase during the Alpha and Omicron waves. Skin-to-skin (mean value 66.2%) had its lowest level at the beginning of the pandemic and gradually increased throughout the study period. Among women who had a caesarean section (n = 1,777; 33.2%), all the indicators showed notably worse outcomes with similar variations in the study period. Multiple logistic regression analyses confirm the observed variations during the pandemic and show a lower adherence to good practices in southern regions and in maternity units with a higher annual number of births. Conclusions Despite the rising trend in the studied indicators, we observed concerning substandard childbirth care during the SARS-CoV-2 pandemic. Continued efforts are necessary to underscore the significance of the experience of care as a vital component in enhancing the quality of family-centred care policies.